Activin Signaling in the Pathogenesis and Therapy of Neuropsychiatric Diseases - Link, Andrea S.; Zheng, Fang; Alzheimer, Christian (Frontiers in Molecular Neuroscience, 2016)
Activins are members of the transforming growth factor β (TGFβ) family and serve as multifunctional regulatory proteins in many tissues and organs. In the brain, activin A, which is formed by two disulfide-linked βA subunits, is recognized as the predominant player in activin signaling. Over the last years, considerable progress has been made in elucidating novel and unexpected functions of activin in the normal and diseased brain and in deciphering the underlying molecular mechanisms. Initially identified as a neurotrophic and -protective factor during development and in several forms of acute injury, the scope of effects of activin A in the adult CNS has been considerably broadened by now. Here, we will highlight recent findings that bear significance for a better understanding of the pathogenesis of various neuropsychiatric diseases and might hold promise for novel therapeutic strategies. While the basal level of activin A in the adult brain is low, significant short-term up-regulation occurs in response to increased neuronal activity. In fact, brief exposure to an enriched environment is already sufficient to considerably strengthen activin signaling. Enhancement of this pathway tunes the performance of glutamatergic and GABAergic synapses in a fashion that impacts on cognitive functions and affective behavior, counteracts death-inducing signals through extrasynaptic NMDA receptors, and stimulates adult neurogenesis in the hippocampus. We will discuss how impaired activin signaling is involved in anxiety disorders, depression, drug dependence, and neurodegenerative diseases such as Alzheimer´s and Parkinson´s, and how regulation of activin signaling might be exploited for therapeutic interventions.